THE INFLUENCE OF CUSTOMER TRUST, PACKAGING, PRODUCT DIVERSIFICATION, AND SERVICE QUALITY ON CONSUMER SATISFACTION AT UD. PURNAMA JATI JEMBER - Salsabila Fara; Suharto, Akhmad; Rahayu, Jekti (Universitas Muhammadiyah Bengkulu, 2025)
The current era of globalization is very rapid, and it has a big impact on the business world. The market is getting wider and the opportunities are also very diverse, this makes business competition even tighter. UD. Purnama Jati is one of the retailers that provide typical food in the Jember area which has been established since 2000. UD. Purnama Jati is widely known by the wider community, which is located at Jl. Bungur No. 9, East Darwo, Gebang, Patrang District, Jember Regency. This study aims to determine the influence of customer trust, packaging, product diversification, and service quality on consumer satisfaction in the tak. The research method used was quantitative descriptive sample used by 95 respondents. The data was collected using questionnaires. The data was processed using multiple linear regression analysis techniques using the SPSS analysis tool version 24. The results of this study show that customer trust, packaging, and product diversification have a significant influence partially on consumer satisfaction. The quality of service does not have a significant influence on consumer satisfaction. This finding is expected to be used as additional information or as input for UD. Purnama Jati in increasing consumer satisfaction